Catalytic wet air oxidation of low molecular weight carboxylic acids using a carbon supported platinum catalyst - Gomes, Helder (2010)
Aqueous solutions of low molecular weight carboxylic acids, such as acetic, propionic and butyric acids, were treated by catalytic wet air oxidation (CWAO) using a carbon supported platinum catalyst. Oxidation in the presence of the catalyst, in a stirred reactor, was carried out at 200 C and 6.9 bar of oxygen partial pressure, with conversions (after 2 h) ranging from 59.4 to 75%, and selectivities to gaseous products of up to 100%. Initial rates for conversion varied from 184 (butyric acid) to 260 mmol h−1 g−1 Pt (propionic acid). The activation energy for butyric acid conversion was found to be 56.7 kJ mol−1.